1972
DOI: 10.1002/1097-0142(197201)29:1<66::aid-cncr2820290112>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosarcoma occurring at the site of a plastic vascular graft

Abstract: A sarcoma, arising in association with a prosthetic arterial graft, was surgically excised. The patient, a 31‐year‐old man, sustained a soft tissue injury to the thigh 10 years previously. A lacerated superficial femoral artery was repaired with a woven teflon‐dacron graft. A large tumor surrounded, but did not invade, the graft. The tumor posed diagnostic difficulties and was thought to be either an angiosarcoma or a fibrosarcoma. Electron microscopy, performed retrospectively, showed the tumor to be probably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

1975
1975
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 7 publications
1
10
0
3
Order By: Relevance
“…Several reports have been published of aortic intimal sarcomas arising in association with Dacron grafts, 7,8,14,16,30,[33][34][35][41][42][43] suggesting an inducing or promoting effect of the foreign material on the endothelium. Oppenheimer et al 31 demonstrated that the implantation of plastic discs in animals could induce fibrosarcoma in the fibrous capsule that forms around the disc.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have been published of aortic intimal sarcomas arising in association with Dacron grafts, 7,8,14,16,30,[33][34][35][41][42][43] suggesting an inducing or promoting effect of the foreign material on the endothelium. Oppenheimer et al 31 demonstrated that the implantation of plastic discs in animals could induce fibrosarcoma in the fibrous capsule that forms around the disc.…”
Section: Discussionmentioning
confidence: 99%
“…22 Some rare cases of soft tissue sarcomas have been reported in surgical scars or in contact with metallic 23 or plastic implants. 5,24 Sarcomas have also been found in animal experimental models in contact with implanted biomaterials. 25 No chemical constituent involved in the composition of metallic alloys used in spinal surgery is clearly recognized as a carcinogen potentially responsible for sarcomatous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between surgical im plants and sarcogenesis has not been clearly dem onstrated, several case reports have described a tem po ral relation ship between the placem en t o f surgical im plants and the successive development of sarcoma. 17,18 T he m ost frequent histotype described was ® brosarcom a 19,20 with rhabdom yosarcom a also described. 21 Recently a patient was reported to have a malignant ® brous histiocytom a in the bone± cement m em brane after revision for a loose total hip prosthesis.…”
Section: Discussionmentioning
confidence: 99%